2013
DOI: 10.3945/jn.113.176636
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sesame Seed and Its Lignan, Sesamin, Increase Tocopherol and Phylloquinone Concentrations in Male Rats1–3

Abstract: We have shown that intake of sesame seed and its lignan increases vitamin E concentrations and decreases urinary excretion levels of vitamin E metabolites in male Wistar rats, suggesting inhibition of vitamin E catabolism by sesame lignan. The aim of this study was to examine whether dietary sesame seed also increased vitamin K concentrations, because its metabolic pathway is similar to that of vitamin E. To test the effect of sesame lignan on vitamin K concentrations, male Wistar rats were fed a control diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
1
17
0
2
Order By: Relevance
“…Although the effect of excess γ‐tocopherol intake in decreasing extrahepatic PK in rats has been observed , α‐tocopherol's potent effect, compared to γ‐tocopherol in experiment 1, in decreasing extrahepatic PK was confirmed (Table ). Despite the equivalent amounts of α‐ and γ‐tocopherol in the diets, α‐tocopherol in tissues from α‐tocopherol‐fed rats was higher than γ‐tocopherol in tissues of γ‐tocopherol‐fed rats (A and G groups, respectively; Table ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although the effect of excess γ‐tocopherol intake in decreasing extrahepatic PK in rats has been observed , α‐tocopherol's potent effect, compared to γ‐tocopherol in experiment 1, in decreasing extrahepatic PK was confirmed (Table ). Despite the equivalent amounts of α‐ and γ‐tocopherol in the diets, α‐tocopherol in tissues from α‐tocopherol‐fed rats was higher than γ‐tocopherol in tissues of γ‐tocopherol‐fed rats (A and G groups, respectively; Table ).…”
Section: Discussionmentioning
confidence: 93%
“…In a study of the effects of sesame lignan in causing increased vitamin K , we have found that, in rats fed PK, intake of excess dietary γ‐tocopherol decreases PK in extrahepatic tissues but not in serum and liver, which led to an interest in possible interactions between vitamins E and K. In this study, first, the effects of dietary α‐ and γ‐tocopherol on PK and MK‐4 concentrations were compared because most human dietary vitamin E is composed mainly of α‐ and γ‐tocopherol. Next, α‐tocopherol consumption‐dependent effects on PK and MK‐4 concentrations in rats fed PK were examined using α‐tocopherol‐free, insufficient, normal, and rich α‐tocopherol diets.…”
Section: Introductionmentioning
confidence: 99%
“…When vitamin E increases the expression or activity of enzymes involved in its own degradation, it is possible that vitamin K metabolism is also enhanced under elevated vitamin E status; this may lead to higher rates of vitamin K excretion and in turn to vitamin K deficiency with enhanced bleeding risk [160] . Evidence for this hypothesis was provided by Hanzawa et al [231] , as rats treated with a diet consisting of 20% sesame seeds, containing sesamin as an inhibitor of vitamin E metabolism, for 40 d had increased vitamin K tissue concentrations. It should be noted that the vitamin E form used in this diet was solely γ-TOH.…”
Section: Interaction With Vitamin K Metabolismmentioning
confidence: 94%
“…세사민은 인체 내에서 뚜렷한 항산화 활 성을 나타낸 것으로 보고되었는데 γ-토코페롤과 협동적으 로 작용하여 쥐에서 비타민 E 활성을 생성하고 α-토코페롤 이 적은 식단을 먹인 쥐에서 뚜렷한 비타민 E 활성 강화효 과가 보고되었다 (Yamashita et al, 1992(Yamashita et al, , 1995. 또한 비타 민 E 뿐만 아니라 비타민 K 활성 강화효과도 보고되었다 (Hanzawa et al, 2013). 또한 세사민은 쥐의 간에서 지방산 산화를 유도하고 sterol regulatory element binding protein-1 을 억제하여 지방산 합성을 감소시킨다고 한다 (Ide et al, 1999(Ide et al, , 2001.…”
unclassified